Dl diesel engine cycle simulation and validation - Sarkar J. (My University, 2025)
In the present investigation, Dl diesel engine cycle simulation code, based on steady-state phenomenological model has been developed. The heat loss to the surrounding, blow-by losses and emission model by using chemical equilibrium, reaction kinetics, and calculation of thermodynamics properties based on their mixture composition were included in this model. The model has been developed to predict the temperature, pressure and exhaust species variation and efficiency at various engine loads. The system has been validated with experimental data.